A Dialogue between Pragmatism and Existentialism: W. James and F. Nietzsche on Truth. - Yılmaz, Reyhan (Problems / Problemos, 2024)
In this article, I elucidate the ways in which pragmatism and existentialism can be viewed as compatible by focusing on the notion of truth. For this purpose, I explore James' pragmatic method and Nietzsche's critical approach to 'will to truth' to reveal the notable link between them. Both thinkers react against the idea of truth as absolute, fixed, and indifferent to individuals' practical needs. Accordingly, they argue that truth, conceived pre-theoretically, is a process immanent to subjects' concrete experiences of life. I critically examine, through pragmatic and existentialistic considerations, how these philosophers question truth within the framework of the individual's existence as an acting agent.